Investigaciones Brasileras sobre los profesores universitarios de química - Lozano, Diana Lineth Parga [UNESP]; Denari, Gabriela Bueno [UNESP] (My University, 2017)
Even though it is important, there are only a few works in science education that deal with academic professors as a research subject. Thus, to contribute to the understanding of researches conducted with these professionals who are so important to the development of an academic career, this work presents a document analysis of the papers published in two Brazilian chemistry teaching events: ENEQ and SIMPEQUI. The researches were categorized from 2008 to 2014 and divided according to their levels of education, in which those of higher education were classified with respect to their research subject. The findings showed a deficiency in the research field, since among more than four thousand papers, the university teacher is the research subject in only thirteen. Even though the discussion about the academic professors is necessary, there have been few studies on the subject in the scientific research.
Teachers of higher education: Analysis of Brazilian publications in chemistry
Keywords: Educational practice; ENEQ; Higher education; SIMPEQUI